Pengembangan Media Pembelajaran Fisika Berbasis Aplikasi Apper Dengan Model Discovery Learning Pada Materi Hukum Newton - Elsi Prisma Katyagni; Elvin Yusliana Ekawati; Rini Budiharti (Jurnal Materi dan Pembelajaran Fisika, 2023)
This study aims to: (1) Describe the characteristics of the Apper application-based Physics learning media with the discovery learning model on Newton's Law material, (2) To find out how experts evaluate Apper application-based Physics learning media with discovery learning models on Newton's Law material based on material aspects , media design and language. The research method used is research and development with the ADDIE research model only in three stages, namely analysis, design and development. Sources of research data were obtained through the results of assessments by 2 supervisors as expert validators, 3 students as peer reviewers, 6 teachers as reviewers, and 72 students. This research was conducted in 2 senior high schools (SMA), namely SMA Negeri 1 Karanganyar and SMA Negeri Kebakkramat. Data types are divided into Qualitative Data and Quantitative Data. Qualitative data obtained from the results of the assessment of suggestions, input and criticism. Quantitative data were obtained from the validation stage, one-on-one trials, small group trials, and large group trials. Data collection techniques using questionnaires. Data analysis was carried out qualitatively and quantitatively based on Azwar's research. The conclusions of this study are: (1) The characteristics of Apper application-based Physics learning media with discovery learning models on Newton's Law material use features such as Guidelines, Competence, Newton I, Newton II, Newton III, Friction, Application, Evaluation , and Information. The application is 167 kB in size and can only be accessed online via a smartphone with a minimum operating system Android 5.0 Lollipop and iOS 8.1, (2) Expert assessment of the Apper application-based Physics learning media with the discovery learning model on Newton's Law material meets the very good category based on material aspects, media design and language.